PENGEMBANGAN MEDIA PEMBELAJARAN PKn BERBASIS MULTIMEDIA INTERAKTIF UNTUK SMP KELAS VIII - Pujiastuti, Desy; Idrus, Ali; Emosda, Emosda (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
Developing media based learning using interactive multimedia applications macromedia director. The purpose of this development is to generate media-based interactive multimedia civics learning that can improve student learning outcomes and fit for use during the learning process Civics. The model of development adopted development model Lee & Owen. Broadly speaking, this development model consists of 5 phases: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. product testing conducted on eighth grade students at SMP Negeri 8 Muaro Jambi. Based on the validation results of both material and media, the overall form of media learning products can be categorized as good, and fit for use as a medium of learning civics. Keyword: Learning Media, Citizenship educat